Adding 1 to a given addend __ + 1 =
8 + 1 = 9
11 + 1 = 12
8 + 1 = 9
3 + 1 = 4
0 + 1 = 1
4 + 1 = 5
2 + 1 = 3
6 + 1 = 7
10 + 1 = 11
5 + 1 = 6
3 + 1 = 4
9 + 1 = 10
5 + 1 = 6
0 + 1 = 1
7 + 1 = 8
9 + 1 = 10
5 + 1 = 6
7 + 1 = 8
0 + 1 = 1
4 + 1 = 5
1 + 1 = 2
6 + 1 = 7
1 + 1 = 2
9 + 1 = 10
10 + 1 = 11
11 + 1 = 12
8 + 1 = 9
1 + 1 = 2
6 + 1 = 7
10 + 1 = 11
4 + 1 = 5
7 + 1 = 8
1 + 1 = 2
2 + 1 = 3
6 + 1 = 7
8 + 1 = 9
2 + 1 = 3
9 + 1 = 10
3 + 1 = 4
11 + 1 = 12
2 + 1 = 3
10 + 1 = 11
3 + 1 = 4
5 + 1 = 6
7 + 1 = 8
11 + 1 = 12